Влияние латинского языка на лексико-семантические процессы в истории русского языка: к постановке проблемы - Наталия Николаева (Studia Rossica Posnaniensia)
Latin influence in the history of Russian was not universal in character; however, it started to be regular in the 16th century, which was reflected both in the lexical system (loanwords) and in semantics (semantic modulation of words). It is important to carry out an in-depth research study on this process because it still has not been thoroughly and systematically studied. This article presents a fragment of such a study as an example.